UPAYA PENINGKATAN HASIL BELAJAR MATEMATIKA SISWA KELAS VI SDN SENTOL 2 MENGGUNAKAN METODE INKUIRI - Zainatul Itsnainiz Zulkha Zulkha; Agung Setyawan (Renjana Pendidikan Dasar, 2022)
The purpose of this study was to determine the increase in students' cognitive learning outcomes in the mathematical content of the volume of geometric figures using the inquiry method in Class VI SDN Sentol 2 Pamekasan. This research was carried out in 2 cycles that applied the class action research design of Kurt Lewin's model, namely planning, implementation, observation, and reflection. In the pre-cycle the average student learning outcomes were 60 with classical learning mastery of 36% and classical absorption of 60%. In the first cycle the average student learning outcomes were 78 with classical learning completeness 57% and classical absorption 78%. While in the second cycle the average student learning outcomes were 92 with 100% classical learning completeness and 92% classical absorption. It can be concluded that the use of the inquiry method can improve student learning outcomes on the mathematical content of the volume of geometric material.